A Hub and Spoke Learning Program in Bariatric Surgery in a Small Region of Italy - Buondonno, Antonio; Avella, Pasquale; Cappuccio, Micaela; Scacchi, Andrea; Vaschetti, Roberto; Di Marzo, Giancarlo; Maida, Pietro; Luciani, Claudio; Amato, Bruno; Brunese, Maria Chiara; Esposito, Daniela; Selvaggi, Lucio; et al. (Frontiers in Surgery, 2022)
Background: Metabolic and Bariatric Surgery (BS) are considered life-changing and life-saving treatments for obese patients. The Italian Society of Obesity Surgery (SICOB) requires at least 25 operations per year to achieve the standard of care in the field. Despite the increasing need to treat obese patients, some small southern regions of Italy, like Molise, do not have enough experience in bariatric procedures to be allowed to perform them. So, our aim is to run a Hub & Spoke program with a referral center in BS to treat obese patients and provide a proper learning curve in BS in Molise. Methods: In the 2020 the “A. Cardarelli Hospital” in Campobasso, Molise, started a formal “Learning Model of Hub & Spoke collaboration” with the Hub center “Ospedale Del Mare”, Naples. A multidisciplinary approach was achieved. Patients were supervised and operated under the supervision and tutoring of the referral center. We retrospectively reviewed our prospectively collected database from February 2020 to August 2021 in order to analyze the safety and effectiveness of our learning program. Results: 13 (3 male and 10 female) patients underwent BS. Mean age of 47.08 years and a pre-surgery BMI of 41.79. 7 (53.84%) patients were ASA II, and 6 (46.16%) patients were ASA III. All procedures were performed laparoscopically. 12 (85.72%) procedures were sleeve gastrectomies and 1 was gastric band removal. 1 (7.14%) patient underwent endoscopic BioEnterics Intragastric Balloon (BIB) placement. Mean surgical time was 110.14 ± 23.54 minutes. Mean length of stay was 4.07 ± 2.40 days. No Clavien-Dindo ≥ III and mortality were reported. The follow-up program showed a mean decreasing of 11.82 in term of BMI value. The last 5 procedures were performed by the whole equips from “A. Cardarelli” under external tutoring without any impact on complication rate. Conclusion: The set-up of a proper Hub & Spoke program may allow to perform BS providing the standard of care. This approach may reduce health costs and related patient migration.